2019
DOI: 10.24925/turjaf.v7i4.652-657.2382
|View full text |Cite
|
Sign up to set email alerts
|

Remote Monitoring of European Grapevine Moth, Lobesia botrana (Lepidoptera: Tortricidae) Population Using Camera-Based Pheromone Traps in Vineyards

Abstract: This study presents a new sex pheromone trap for European Grapevine Moth, Lobesia botrana, to monitor its field population without direct field observations in Turkey. The study was conducted in Hadim and Taşkent (Konya) districts in 2016. Viticulture has been carried out for many years in both districts where the maximum vineyards are located. Due to the distance to the center and the difficulty of transportation to these districts, there has not been conducted any detailed studies until today. Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Trapview traps, iSCOUT traps, SightTrap traps, Z‐Trap 1, and DTN Smart Trap traps 17–20 . Similarly, a number of smart trap prototypes have been investigated for monitoring tortricid orchard pests, including codling moth, oriental fruit moth, Grapholita molesta (Busck), and European grapevine moth, Lobesia botrana (Denis and Schiffermüller) (Lepidoptera: Tortricidae) 21–23 . However, these experimental studies have only used traps baited with sex pheromone lures and captures of nontargets in these traps has not been reported to be a serious issue.…”
Section: Introductionmentioning
confidence: 99%
“…Trapview traps, iSCOUT traps, SightTrap traps, Z‐Trap 1, and DTN Smart Trap traps 17–20 . Similarly, a number of smart trap prototypes have been investigated for monitoring tortricid orchard pests, including codling moth, oriental fruit moth, Grapholita molesta (Busck), and European grapevine moth, Lobesia botrana (Denis and Schiffermüller) (Lepidoptera: Tortricidae) 21–23 . However, these experimental studies have only used traps baited with sex pheromone lures and captures of nontargets in these traps has not been reported to be a serious issue.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the major limitation of taking repeated shots is power consumption, which is mainly related to data transmission. Therefore, the automatic traps developed to date are typically set to take a daily picture (Guarnieri et al 2011;Ünlü et al 2019). However, multiple shots, including up to three photos per day, have been reported for experimental prototypes (Rassati et al 2016), such as those recently available for Trapview® (EFOS d.o.o, Hruševje, Slovenia) commercial automatic traps (Trapview 2020).…”
Section: Picture Acquisitionmentioning
confidence: 99%
“…In some of the case studies reported here (Guarnieri et al 2011;Rassati et al 2016;Shaked et al 2018;Ünlü et al 2019), the captured insects were checked manually by remote, and the images were observed by the human eye via computer or smartphone. This approach requires a trained observer in the control station to properly identify the insect species, and despite actually avoiding the field visit, the process is time-consuming.…”
Section: Insect Pest Identification and Countmentioning
confidence: 99%
“…The use of automated image capture technology to monitor insect pest populations in applied research experiments [5][6][7] and commercial settings [8][9][10][11][12] has proven effective for timely pest management in various cultivated crop systems, including vineyards. Many of these image capture technologies facilitate automated image acquisition of traps that are set at a fixed distance and within optimal focus.…”
Section: Related Workmentioning
confidence: 99%
“…Some of these automated insect trap setups ensure that the acquired images are free from shadows or specular reflections to enable remote insect identification and automate pest enumeration [7,13]. However, some automated trap setups still rely on static systems that require proprietary traps or enclosures, where the sticky trap must be assembled [5,6].…”
Section: Related Workmentioning
confidence: 99%